Sistem Pelapisan Sosial Masyarakat Perkebunan Teh Kertowono, Kecamatan Gucialit, Kabupaten Lumajang - Girindrawardani, Anak Agung Ayu Dewi (Sunari Penjor : Journal of Anthropology, 2024)
Although various plantations throughout Indonesia have been established since the era of independence, the social system, especially the social stratification system, still forms patterns of relationships between social classes with characteristics that have remained relatively stable since the plantation system was established by the colonialists. Likewise, what happened in the Kertowono tea plantation community, Gucialit District, Lumajang Regency, can be divided into three social classes, namely the upper, middle and lower classes, which gave rise to strict patterns of social relations in society that formed patron-client relationships. The research was conducted using an ethnographic approach method as one of the variants of the qualitative approach. Research activities include field exploration to understand the conditions of the research location, followed by field data collection using interview techniques, observation, literature, and document examination. Data collected from various sources are then processed, analyzed, and then presented in the form of descriptive descriptions. Research shows social stratification that occurs in society and patterns of social relations in plantation communities that can be seen from 4 patterns of relations, namely (a) patterns of social relations in the community; (b) patterns of relations in economic institutions; (c) patterns of relations in kinship institutions; (d) patterns of relations in religious institutions.